Digital tools for qualitative research - Paulus, Trena M.; Lester, Jessica Nina; Dempster, Paul G. (Los Angeles SAGE, 2014)
Digital Tools for Qualitative Research shows how the research process in its entirety can be supported by technology tools in ways that can save time and add robustness and depth to qualitative work. It addresses the use of a variety of tools (many of which may already be familiar to you) to support every phase of the research process, providing practical case studies taken from real world research.
Companion website -- 1 Why digital tools? -- 2 Engaging in reflexive practice and making ethical choices -- 3. Collaborating and managing projects -- 4 Reviewing the literature -- 5 Generating data -- 6 Transcribing audio and video data -- 7 Analysing textual data -- 8 Analysing image, audio and video data -- 9 Writing and representing findings -- 10 Looking to the future.
Includes bibliographical references and index.
Keywords: Qualitative research -- Data processing